The Impacts of Medical Career Day to Medical Students' Interest to Pursue a Career in Public Health - Rio Yus Ramadhani; Rizma Adlia Syakurah; Mariatul Fadilah (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2017)
Background: Medical career day is one of the activities to introduce career options that exist and increase interest in a particular career. This study aims to determine the effect of material medical career day activities to increase the interest of medical students to pursue a career to the field of public health sciences.Method: This study is a quasi-experimental study with pretest-posttest control group design. The control group received counseling about the field of public health sciences, whereas the intervention group receive the same counseling accompanied by a description of the activity-based cost and opportunity cost in the field of public health sciences. The study population was 216 students of medical faculty batch 2014. Out of 216 students, 70 met the inclusion criteria, and only 36 who came to the activity. Data analysis was performed using paired t-test.Results: Thirty-six students came to the medical career day activities are divided into 2 groups: the first 18 people who come into the intervention group and 18 others to a control group. Increased interest in the control group (p=0.003) and increased interest in the intervention group was also significant (p=0.023).Conclusion: Material medical career day activities plus activity based cost and opportunity cost may increase the interest of students to pursue a career to the field of public health sciences.